Real Estate Development in the Ski Resorts of the Tarentaise Valley - Gabriel Fablet (Revue de Géographie Alpine)
In the context of a mature winter sports market and ageing accommodation facilities, most contemporary French ski resorts are having to deal with a gradual decline in visitor numbers. Faced with the failure of numerous attempts to introduce rehabilitation measures, new property developments appear the only way to maintain a viable tourism economy in these mountain areas. The purpose of this paper is to gain insights into the real estate development process in ski resorts. Based on the example of the Tarentaise Valley, the paper focuses on the seemingly headlong rush of many resorts into real estate construction. More generally, it analyzes the characteristics of an economic model that is structurally dependent on permanent urban development to ensure its viability.